PEACEFUL LIFE LEARNING ABOUT TENGGER CULTURE AND ITS CHALLENGES - Suwarta, Nyoman; Riyanto, Edi Dwi; Santoso, Listiono (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the current life habitus of the Tengger Indigenous People amid the growing tourism industry in the Bromo area. Method: Employing a qualitative approach, data were collected through observation, in-depth interviews, and focus group discussions (FGDs), then analyzed using a social and cultural reproduction framework. Results: The findings reveal five core habitus that characterize the Tengger Indigenous lifestyle: Maintaining Politeness, Obeying the Rules, Straightforward and Relatively Smooth Language, Simple Reasoning, and Peaceful Living. However, transformations—referred to as a “shock” to the habitus—have emerged, triggered by external influences such as the ownership of luxury vehicles, culturally insensitive behavior by foreign tourists, and the discovery of illicit drug cultivation. These phenomena indicate social tensions disrupting the community’s traditional harmony. Novelty: This research offers a comprehensive understanding of the transformation in indigenous cultural habitus due to tourism, emphasizing the urgent need for balanced and respectful interactions among stakeholders in the TNBTS area to preserve traditional values while accommodating modern demands.